The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1253/circj.cj-09-0535
|View full text |Cite
|
Sign up to set email alerts
|

The Role of N-Terminal Pro-B-Type Natriuretic Peptide in the Diagnosis of Congestive Heart Failure in Children - Correlation With the Heart Failure Score and Comparison With B-Type Natriuretic Peptide -

Abstract: Background: Both B-type natriuretic peptide (BNP) and N-terminal pro-BNP (NT-proBNP) are useful biomarkers for the assessment of congestive heart failure (CHF) in adults. The purpose of this study was to determine whether BNP and NT-proBNP levels could be used to stratify the severity of CHF in children. Methods and Results:The study comprised 181 children with CHF and 232 healthy children aged from 4 months to 14 years who were categorized into CHF grades I, II, III and IV according to the modified Ross scori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 35 publications
(16 reference statements)
5
40
1
Order By: Relevance
“…The uniform diagnostic tool for heart failure may have accounted for the similarity in findings. However, unlike other studies (11,17,18) the relationship between plasma NT-proBNP and the severity of heart failure in this study was not uniform as the subjects with moderate heart failure had a lower mean plasma NT-proBNP compared to those with mild heart failure. This may be due to the fact that infants who tend to have higher NT-proBNP values (27) contributed more to subjects with mild and severe forms of heart failure in contrast to those with moderate heart The mortality rate in this study was 3.2% which is lower than the 5.34% reported previously by Sadoh et al (30) in the same study area and 11.1% by Anah and co-workers (5).…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The uniform diagnostic tool for heart failure may have accounted for the similarity in findings. However, unlike other studies (11,17,18) the relationship between plasma NT-proBNP and the severity of heart failure in this study was not uniform as the subjects with moderate heart failure had a lower mean plasma NT-proBNP compared to those with mild heart failure. This may be due to the fact that infants who tend to have higher NT-proBNP values (27) contributed more to subjects with mild and severe forms of heart failure in contrast to those with moderate heart The mortality rate in this study was 3.2% which is lower than the 5.34% reported previously by Sadoh et al (30) in the same study area and 11.1% by Anah and co-workers (5).…”
Section: Discussioncontrasting
confidence: 98%
“…(ng/L being the same as pg/mL) Subjects with severe heart failure had significantly higher mean NT-proBNP value compared to mild and moderate categories. This finding is akin to reports by Ekure et al (18), and Sugimoto et al (11) both noted an increasing plasma NT-proBNP with worsening degree of heart failure. The uniform diagnostic tool for heart failure may have accounted for the similarity in findings.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…15 Similar studies on children have equally shown that plasma levels of NT-proBNP are good for diagnosing heart failure and may be used as a screening test. [16][17][18] Wu et al in China reported a sensitivity and specificity of 89.3% and 91.2% respectively when plasma NTproBNP was used to diagnose congestive cardiac failure in children with ventricular septal defect. 16 We note that the sensitivity in our report is significantly lower at 57%.…”
Section: E N Ekure and Associates N-terminal Pro-brain Natriuretic mentioning
confidence: 99%